(untitled) (The Peerian Journal, 2023)
The joint efforts of the coach and the athlete make it possible to effectively control the training process, achieve the highest sports results. In the present day highly qualified tourists often due to objective conditions are preparing independently. The preparation of a tourism campaign for the management of the sports complex sessions must know.